2021
DOI: 10.1101/2021.02.03.429553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specialization and selective social attention establishes the balance between individual and social learning

Abstract: A key question individuals face in any social learning environment is when to innovate alone and when to imitate others. Previous simulation results have found that the best performing groups exhibit an intermediate balance, yet it is still largely unknown how individuals collectively negotiate this balance. We use an immersive collective foraging experiment, implemented in the Minecraft game engine, facilitating unprecedented access to spatial trajectories and visual field data. The virtual environment impose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Furthermore, as recently demonstrated by Wu et al. ( 2021 ), in random, dynamic environments, people are less reliant on observing others to obtain information, while balancing individual and social learning to avoid correlated social information and maladaptive information cascades. This may be beneficial if—as our results suggest—common trends seen in social information may systematically arise from the behavior of those individuals who are relatively poorly informed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, as recently demonstrated by Wu et al. ( 2021 ), in random, dynamic environments, people are less reliant on observing others to obtain information, while balancing individual and social learning to avoid correlated social information and maladaptive information cascades. This may be beneficial if—as our results suggest—common trends seen in social information may systematically arise from the behavior of those individuals who are relatively poorly informed.…”
Section: Discussionmentioning
confidence: 93%
“…This may be related to the work of Findling et al (2019), who found computational noise to be a core feature of learning, and suggested that an increase in that noise accompanying a high learning rate could be a significant source of behavioral variability in reward-guided decisions. Furthermore, as recently demonstrated by Wu et al (2021), in random, dynamic environments, people are less reliant on observing others to obtain information, while balancing individual and social learning to avoid correlated social information and maladaptive information cascades. This may be beneficial if-as our results suggest-common trends seen in social information may systematically arise from the behavior of those individuals who are relatively poorly informed.…”
Section: Discussionmentioning
confidence: 99%
“…One way that humans mitigate the risks of decision-making under uncertainty, is by using problem-solving heuristics or rules-of-thumb that are based on previous experience with similar situations 10,11 and are subject to individual differences . Specifically, in problem spaces or environments which change often or are otherwise uncertain, alternative strategies may be sampled frequently 47,48 or reliance on other sources of information, like socially-acquired strategies can increase 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results predict that higher explorative/innovative tendencies can improve a group's problem-solving capabilities in a rugged or complex problem-space where multiple solutions need to be discovered. However, pure exploratory strategies need to be balanced with social learning in complex spaces to focus a group's effort on the solutions already found and optimize the search (Fang et al, 2010;Miu et al, 2020;Wu et al). By contrast, when the problem spaces are 'simple'…”
Section: Discussionmentioning
confidence: 99%